2021
DOI: 10.1111/exsy.12801
|View full text |Cite
|
Sign up to set email alerts
|

Autism diagnosis via correlation between vectors of direct quadrature instantaneous frequency of EEG analytic normalized intrinsic mode functions

Abstract: Autism spectrum disorder (ASD) is a neurological and developmental disorder that commences usually in the early years of age. It impacts the social interaction, communication and learning. It is believed that it is mainly caused by an abnormal connectivity between brain zones. The presented work applies an EEG‐based nonlinear method for the classification of ASD and neuro‐typical groups. The suggested procedure does not require pre‐assumptions and is completely data‐driven. Also, the main advantage is the accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Artificial intelligence is a tool that finds its way into a wide variety of applications from material science, and environmental applications, to smart health care systems. ,,,, Draz et al reported the development of nanoparticles-enabled smartphones for the detection of the virus using artificial intelligence . The system consists of a microchip for capturing the virus using specifically designed platinum nanoprobes.…”
Section: Artificial Intelligence For Diagnosis Of Infectious Diseasesmentioning
confidence: 99%
“…Artificial intelligence is a tool that finds its way into a wide variety of applications from material science, and environmental applications, to smart health care systems. ,,,, Draz et al reported the development of nanoparticles-enabled smartphones for the detection of the virus using artificial intelligence . The system consists of a microchip for capturing the virus using specifically designed platinum nanoprobes.…”
Section: Artificial Intelligence For Diagnosis Of Infectious Diseasesmentioning
confidence: 99%